Hematological and thrombotic manifestations in patients with suspected viral pneumonia during the COVID-19 pandemic at Tishreen University Hospital in Lattakia. - حسين , فراس; حمدان , لجين; حمدان , صبا; محمد , كندا; كفى , ريم; معروف, علاء (Latakia University Journal -Medical Sciences Series, 2022)
Background: Since December 2019, Coronavirus has been spreading widely until it became a fatal global pandemic. We’re currently in a great need to determine early and effective predictive biomarkers for the severity and mortality, in order to understand the pathophysiological mechanisms of the disease, and to find better treatment approaches. Object: Studying the hematologic and thrombotic manifestations in patients with COVID-19 on admission, and investigating their effects on prognosis Methods: Samples were collected from the COVID department of Tishreen University Hospital in Latakia from May 2020 to December 2020. Samples were sequentially included according to admission date, and classified into one of the two study groups based on the results of COVID-19 nasal swab test, characterization of demographic variables (age and gender), clinical and radiologic severity upon admission, in addition to the laboratory results. Patients' clinical progress was followed up during hospitalization, as well as their need for supportive oxygen (invasive and non-invasive mechanical ventilation) and the occurrence of complications during hospitalization, especially thrombotic complications. Finally, we listed the cases of recovery and death Results: The sample included 527 patients. A PCR test was performed, which was positive for COVID-19 in 284 cases; 194 males and 90 females. Patients aged between 27 and 92 years, with a mean age of 65. Each variable was studied in relation to clinical, radiologic severity and death. We found that lymphocytopenia on admission was associated with an increased clinical severity (P-value = 0.002) and a higher mortality (P-value = 0.02). Higher PCT values on admission were associated with an increased clinical severity (P-value = 0.009) and a higher mortality (P-value = 0.03). A higher neutrophil to lymphocyte ratio was associated with an increased clinical and radiologic severity, and a higher mortality (P-value = 0.0001). As for the increase in the platelet to lymphocyte ratio, it was associated with a more severe illness; clinically (P-value = 0.0001) and radiologically (P-value = 0.0001), as well as a higher mortality (P-value = 0.006). Higher D-Dimer values were associated with a more severe illness, both clinically (P-value = 0.0001) and radiologically (P-value = 0.007), as well as a higher mortality (P-value = 0.0001). In addition, we found a cut-off value for D-dimer of 695.5 ng/ml, which may early predict in-hospital mortality. Finally, high risk COVID-19 patients who subsequently developed thrombotic events (such as pulmonary embolus – arterial thrombosis) or required mechanical ventilation had elevated D-Dimer and prolonged PT values on admission; by a significant margin than mild and moderately severe cases. Conclusion: Comprehensive laboratory tests must be performed for COVID patients upon admission; the most important of which are: WBC – PCT – D-Dimer – PT. This helps to identify high risk patients in order to provide them with early intensive care, as they’re more likely to develop severe infections and are candidates for serious thrombotic and respiratory complications. Appropriate therapeutic anticoagulants should be started early for these patients. Regular radiologic scanning (Chest CT with contrast – Doppler ultrasonography) should also be performed to detect these complications early and treat them appropriately. We suggest conducting future studies on D-Dimer in order to find a more accurate cut-off value as a predictive indicator for mortality.